Potent and selective Bruton's tyrosine kinase inhibitors: Discovery of GDC-0834. Issue 6 (15th March 2015) - Young, Wendy B.; Barbosa, James; Blomgren, Peter; Bremer, Meire C.; Crawford, James J.; Dambach, Donna; Gallion, Steve; Hymowitz, Sarah G.; Kropf, Jeffrey E.; Lee, Seung H.; Liu, Lichuan; Lubach, Joseph W.; et al.
Graphical abstract: Abstract: SAR studies focused on improving the pharmacokinetic (PK) properties of the previously reported potent and selective Btk inhibitor CGI-1746 (1 ) resulted in the clinical candidate GDC-0834 (2), which retained the potency and selectivity of CGI-1746, but with much improved PK in preclinical animal models. Structure based design efforts drove this work as modifications to1 were investigated at both the solvent exposed region as well as 'H3 binding pocket'. However, in vitro metabolic evaluation of2 revealed a non CYP-mediated metabolic process that was more prevalent in human than preclinical species (mouse, rat, dog, cyno), leading to a high-level of uncertainly in predicting human pharmacokinetics. Due to its promising potency, selectivity, and preclinical efficacy, a single dose IND was filed and2 was taken in to a single dose phase I trial in healthy volunteers to quickly evaluate the human pharmacokinetics. In human, 2 was found to be highly labile at the exo-cyclic amide bond that links the tetrahydrobenzothiophene moiety to the central aniline ring, resulting in insufficient parent drug exposure. This information informed the back-up program and discovery of improved inhibitors.